The role of the Turkish military establishment in Political life (Journal of the College of Basic Education, 2022)
The Turkish military institution is one of the strongest and most organized institutions of the Turkish stateIf it is not, in fact, a supreme authority that lies above the constitution and other state institutions, including bodieselected; This institution derives its importance and strength from the tight internal organization of this institutionIt enjoys complete independence in selecting its leadership elements and has a clear vision of its rolethe supreme goals of the state; In addition to the huge numerical strength of the Turkish Armed Forces ©So that it comes according to this criterion in the second place after America among the NATO countries.Over time, the military was able to establish a non-military elite in the countrybureaucracy and intellectuals;